Continuous flow catalysis with CuBTC improves reaction time for synthesis of xanthene derivatives - Thai, Jonathan E.; Roach, Madeline C.; Reynolds, Melissa M. (Frontiers in Chemistry, 2023)
The copper-based metal-organic framework (MOF) CuBTC (where H3BTC = benzene-1,3,5-tricarboxylate) has been shown to be an efficient heterogeneous catalyst for the generation of 1,8-dioxo-octa-hydro xanthene derivatives, which are valuable synthetic targets for the pharmaceutical industry. We have applied this catalytic capability of CuBTC to a continuous flow system to produce the open chain form of 3,3,6,6-tetramethyl-9-phenyl-3,4,5,6,7,9-hexahydro-1H-xanthene-1,8(2H)-dione, a xanthene derivative from benzaldehyde and dimedone. An acid work-up after producing the open chain form of the xanthene derivative was used to achieve ring closure and form the final xanthene product. The CuBTC used to catalyze the reaction under continuous flow was confirmed to be stable throughout this process via analysis by SEM, pXRD, and FT-IR spectroscopy, elemental analysis, and XPS. The reaction to produce the open-chain form of the xanthene derivative produced an average yield of 33% ± 14% under the continuous flow (compared to 33% ± 0.12% of performing it under batch conditions). Based on the data obtained from this work, the continuous flow system required 22.5x less time to produce the desired xanthene derivative at comparable yields to batch reaction conditions. These results would allow for the xanthene derivative to be produced much faster, at a lower cost, and require less personal time while also removing the need to perform catalyst remove post reaction.